Projection of Traumatic Experience in Abdulrazak Gurnah’s Afterlives - Banu, Farzana; Talukdar, Susmita (Mindscape: A Journal of English & Cultural Studies, 2025)
The enduring legacy of colonialism continues to shape postcolonial societies not through political and economic structures but also through psychological trauma. In Abdulrazak Gurnah’s Afterlives, the psychological wounds imposed by imperial violence are realistically illustrated through the fragmented identities of male characters navigating war, loss, and cultural dislocations. This study explores the lasting psychological impact of trauma on the male characters in Gurnah’s Afterlives through the theoretical framework of trauma studies. Focusing on Khalifa, Hamza and Iliyas, the central characters of the novel, the paper examines how personal and collective traumas that have been rooted in colonial violence, forced displacement, familial separation and cultural dislocation affect their identity formation, emotional stability, and memory. These characters encounter fragmentations, shaped by historical trauma, where the psychological wounds of enslavement and war persist long after the event themselves. This study analyses how trauma in Afterlives is not just an individual psychological experience but also a cultural and historical phenomenon that exposes the silent, long-term impact of empire. Through Gurnah’s narrative it is revealed how the inter-generational transmission of pain and the silencing of traumatic memories in postcolonial trauma discourse, emphasized the complexity that existed as a link between personal suffering and structural violence.